Amine-containing yolk-shell structured magnetic organosilica nanocomposite as a highly efficient catalyst for the Knoevenagel reaction - Neysi, Maryam; Elhamifar, Dawood (Frontiers in Chemistry, 2024)
The yolk-shell structured silica nanocomposites have been considered by many researchers due to their specific physical and chemical properties. These materials have been widely used in adsorption and catalysis processes. Especially, the void space of yolk−shell nanostructures can provide a unique environment for storage, compartmentation, and confinement in host−guest interactions. In this paper, for the first time, the preparation, characterization, and catalytic application of a novel amine-containing magnetic methylene-based periodic mesoporous organosilica with yolk-shell structure (YS-MPMO/pr-NH2) are developed. The MPMO nanocomposite was synthesized through surfactant-directed co-condensation of bis(triethoxysilyl)methane (BTEM) and tetraethoxysilane (TEOS) around Fe3O4 nanoparticles. After Soxhlet extraction, the surface of YS-MPMO nanocomposite was modified with 3-aminopropyl trimethoxysilane to deliver YS-MPMO-pr-NH2 nanocatalyst. This catalyst was characterized by using EDX, FT-IR, VSM, TGA, XRD, nitrogen-sorption, and SEM analyses. The catalytic activity of YS-MPMO/pr-NH2 was studied in the Knoevenagel reaction giving the corresponding products in a high yield and selectivity. The YS-MPMO/pr-NH2 nanocatalyst was recovered and reused at least four times without a significant decrease in efficiency and activity. A leaching test was performed to study the nature of the catalyst during reaction conditions Also, the catalytic performance of our designed nanocomposite was compared with some of the previous catalysts used in the Knoevenagel reaction.